The Joint Effect of Renal Function Status and Coagulation Biomarkers on In‐Hospital Outcomes in Acute Ischemic Stroke Patients With Intravenous Thrombolysis - Manli Lu; Junwen Xue; Yi Wang; Dongqin Chen; Yongjun Cao; Chongke Zhong; Xia Zhang (Immunity, Inflammation and Disease)
ABSTRACT Objective To demonstrate whether combining renal function status [estimating glomerular filtration rate (eGFR)] with coagulation biomarkers [fibrinogen (Fg) and d‐dimer] is more beneficial in predicting in‐hospital outcomes following intravenous thrombolysis (IVT) in acute ischemic stroke (AIS) patients. Methods We studied 417 AIS patients with IVT. According to the cut‐offs of coagulation biomarkers (Fg and d‐dimer) and eGFR determined by receiver operating characteristic (ROC) curves, the patients were divided into four groups: LFLG (low Fg and low eGFR), LFHG (low Fg and high eGFR), HFLG (high Fg and low eGFR), and HFHG (high Fg and high eGFR); or LDLG (low d‐dimer and low eGFR), LDHG (low d‐dimer and high eGFR), HDLG (high d‐dimer and low eGFR), and HDHG (high d‐dimer and high eGFR). Logistic regression models were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for poor outcomes at discharge and post‐stroke pneumonia across the four groups. Results The patients in the HFLG and HDLG groups had the poorest prognosis at discharge and the highest risk of in‐hospital pneumonia. They experienced 3.00 or 4.59 times higher risk of in‐hospital pneumonia than those in the LFHG and LDHG groups (95%CI: 1.07–8.44, p < 0.05; 95%CI: 1.58–13.32, p = 0.005). Similarly, the risk of adverse outcome at discharge was 3.02 and 1.52 times higher in HFLG and HDLG groups (95%CI: 1.63–9.91, p < 0.005; 95%CI: 1.11–5.74, p < 0.05) compared to that in LFHG and LDHG groups. Adding eGFR and Fg or d‐dimer to the risk model improved the risk reclassification for in‐hospital pneumonia and functional outcomes at discharge. Conclusion Combining renal function status and coagulation biomarkers within 4.5 h after onset could better predict in‐hospital outcomes of AIS patients with IVT.